The Combat Zone : murder, race, and Boston's struggle for justice - Brogan, Jan (Bright Leaf, an imprint of University of Massachusetts Press, 2021)
"At the end of the 1976 football season, more than thirty Harvard athletes went to Boston's Combat Zone to celebrate. In the city's adult entertainment district, drugs and prostitution ran rampant, violent crime was commonplace, and corrupt police turned the other way. At the end of the night, Italian American star athlete Andy Puopolo, raised in the city's North End, was murdered in a stabbing. Three African American men were accused of the crime. His murder made national news and led to the eventual demise of the city's red-light district. Starting with this brutal murder, The Combat Zone tells the story of the Puopolo family's struggle with both a devastating loss and a criminal justice system that produced two trials with opposing verdicts, all within the context of a racially divided Boston. Brogan traces the contentious relationship between Boston's segregated neighborhoods during the busing crisis; shines a light on the overtly racist court system that allowed lawyers to strike potential jurors based on their ethnic identity; and lays bare the deep-seated corruption within the police department and throughout the Combat Zone. What emerges is a fascinating snapshot of the city at a transitional moment in its recent past"--